2021
DOI: 10.1038/s41396-020-00883-w
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton carcasses stimulate microbial turnover of allochthonous particulate organic matter

Abstract: Carbon turnover in aquatic environments is dependent on biochemical properties of organic matter (OM) and its degradability by the surrounding microbial community. Non-additive interactive effects represent a mechanism where the degradation of biochemically persistent OM is stimulated by the provision of bioavailable OM to the degrading microbial community. Whilst this is well established in terrestrial systems, whether it occurs in aquatic ecosystems remains subject to debate. We hypothesised that OM from zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Proteinase K digestion in CTAB buffer was followed by chlorophorm-phenol extraction. Nucleic acids were precipitated in PEG 6000 using LPA-carrier and recovered and washed repeatedly with 95% and 70% ethanol before resuspension in water [51]. QC was performed via spectroscopy (Nanodrop, Thermo Fisher) and gel electrophoreses.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Proteinase K digestion in CTAB buffer was followed by chlorophorm-phenol extraction. Nucleic acids were precipitated in PEG 6000 using LPA-carrier and recovered and washed repeatedly with 95% and 70% ethanol before resuspension in water [51]. QC was performed via spectroscopy (Nanodrop, Thermo Fisher) and gel electrophoreses.…”
Section: Dna Extractionmentioning
confidence: 99%
“…the internal structure of the material, and in accordance with previous studies investigating reactivities of allochthonous vs. autochthonous PM. 6,9 Allochthonous OM (e.g., terrestrial leaves) have more support tissues and are rich in complex structural compounds, e.g. lignin and cellulose, which are highly resistant to enzymatic breakdown by microorganisms, as specic, energetically expensive enzymes for microbial utilization are required.…”
Section: Sediment Composition and Binding Mechanisms Of Oc And Fementioning
confidence: 99%
“…[5][6][7] However, recent studies have also demonstrated that highly bioavailable OM such as aquatic plankton can enhance the microbial degradation of structurally complex OM; such as terrestrial substrates, which is described as 'positive priming'. 8,9 The 'priming effect' itself describes non-additive effects on OM degradation aer combining sources of contrasting bioavailability. 10,11 Physical breakdown of OM preceding biodegradation includes leaching, during which inorganic elements (Ca, K, Mg) and simple organic compounds are released.…”
Section: Introductionmentioning
confidence: 99%
“…POM varies in size and composition, ranging from phytodetritus (Rice et al., 1986), larvacean houses (Robison et al., 2005) and faecal pellets (Turner, 2002) to mucilaginous aggregates (Martín & Miquel, 2010). The downward flux of organic material is further affected by the regional and seasonal variability in export flux (de Melo Viríssimo et al., 2022; Lutz et al., 2007; Poff et al., 2021), the size, shape, and composition of the POM (De La Rocha et al., 2008; Kriest, 2002; Omand et al., 2020), the interaction with microbes and/or zooplankton (Cavan et al., 2021; Neubauer et al., 2021), physical processes of aggregation/disaggregation of particles (Burd & Jackson, 2009; Iversen & Ploug, 2010), and ventilation/advection through deep‐ocean circulation (Chunhui et al., 2020). According to biogeochemical models (e.g., Ichino et al., 2015), the export of sinking OM of photosynthetic origin to hadal depths (>6,000 m below sea level) is expected to be low.…”
Section: Introductionmentioning
confidence: 99%